Big data: "Navigating the Hadoop ecosystem: Unraveling the potential of big data” - Saloni Kumari (International Journal of Engineering and Technology, 2023)
Big data refers to extremely large data sets that can be analyzed to reveal patterns, trends, and associations, particularly those relating to hu-man behavior and interactions. This data is too large and complex to be processed using traditional data processing methods, necessitating the use of specialized software and systems to manage and analyze it. This paper discusses about the Big Data Architecture, Hadoop Ecosystem, HDFS, Map reduce, Yarn, Hive, and many other components of Hadoop ecosystem.